Technical and Profitability Aspect of Blue Mosaic Guppy (Poecila reticulata) in Swasti Farm, Sleman, Yogyakarta - Diah Ayu Satyari Utami; Wahyu; Ayudya Wildiani (Department of Aquaculture, 2025)
The blue mosaic guppy (Poecilia reticulata), a highly sought-after freshwater ornamental fish, faces growing market demand. This study evaluates the technical feasibility and profitability of blue mosaic guppy production at Swasti Farm in Sleman, Yogyakarta, Indonesia. Using a case study approach, data were collected through participatory observation, direct monitoring, and semi-structured interviews. Technical performance was assessed by benchmarking farm practices against Indonesian National Standards (SNI 8228.3:2015, SNI 9308:2024) and existing literature. Profitability analysis utilized a one-year business projection model incorporating key metrics: Revenue-to-Cost (R/C), net profit (NP), Break-Even Point by sales volume (BEPs) and production units (BEPu), and Profitability Rate (PR). Production followed four stages: broodstock rearing, breeding, fry/nursery rearing, and harvesting. Rigorous water quality and fish health management ensured protocol compliance. Broodstock (aged three months at spawning) were maintained at a 1:2 male-to-female ratio, yielding 20 larvae per cycle and a 55% survival rate post-nursery. Financial analysis revealed an annual net profit of IDR 9,826,417, with R/C = 1.3, BEPs = IDR 24,419,940, BEPu = 70 fish pairs, and PR = 141%, confirming economic viability. To enhance profitability, scaling production by 75% (to ≥210 fish pairs annually) and optimizing operational efficiencies could elevate profits above Sleman, Yogyakarta’s minimum wage threshold. Findings demonstrate that standardized practices and strategic scaling align guppy farming with regional economic benchmarks, offering a replicable model for small-scale aquaculture ventures.